Influence of well trajectory measurement errors on deviation of its design geometry - Morozov Sergey; Kudryavtsev Ilya; Dokshanin Sergey; Kolotov Andrey; Mityaev Alexander (EPJ Web of Conferences)
The strength and durability of drillstrings is largely determined by bending stresses, which are calculated on the basis of the primary data of its trajectory: measured depth, inclination, azimuth. Each of these values may have some deviation from its value caused by both the error of the measuring device of the drillstring and the gradual increase in the diameter of the open hole due to friction, washing, etc. The work is aimed at establishing the effect of errors in determining the primary data of the well trajectory on the further calculation of its geometric parameters. The paper discusses typical well shapes and the effects of given trajectory parameter errors on the coordinates of its points and curvature, which are then used to calculate bending stresses used to assess the strength and durability of all elements of the drillstring. The results of calculations show that the resulting deviation of curvature in the worst case can be approximately equal to the algebraic sum of errors of the three primary trajectory parameters.